2020
DOI: 10.1007/s13369-020-04839-2
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Rumors on Social Media Based on a CNN Deep Learning Technique

Abstract: Currently, it is easy to create content and share it via social media platforms such as Twitter, Facebook, and Sina Weibo. However, some problems can occur when the shared content includes untrustworthy or misleading information. Thus, researchers from different domains have tried to investigate the impact of rumors on the global community. Several machine learning approaches have been used to detect rumors at their early stage. However, the achieved accuracies demonstrate that the existing state-of-the-art ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…LSTM holds the connection between various words in these sequences. Al-Sarem et al [24] [26]. It leverages a GCN to learn the patterns of rumor propagation.…”
Section: B Deep Learning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LSTM holds the connection between various words in these sequences. Al-Sarem et al [24] [26]. It leverages a GCN to learn the patterns of rumor propagation.…”
Section: B Deep Learning Methodsmentioning
confidence: 99%
“…However, a number of studies used embedding techniques and shown remarkable results. Embedding techniques can capture word associations and improve prediction accuracy [24,26,29]. Word embedding is one of the most popular techniques to represent text vocabulary.…”
Section: B Embedding Layermentioning
confidence: 99%
“…Recently, artificial intelligence (AI) tools, such as machine learning (ML) and deep learning (DL), along with the development of other techniques, such as the Internet of Things (IoT), has attracted several researchers because of their efficiency in various fields like rumor detection in social media [2], natural language processing [3,4], plant disease detection [5,6], smart energy economy and management [7][8][9], civil engineering systems [10,11], and educational system analysis and assessment [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial Intelligence (AI) techniques have been widely used in many applications such as handwriting recognition [5], rumors or fake news detection in social media [6,7], medical diagnosis support systems (MDSS) [8,9], prediction of patients with heart disease [10][11][12][13][14], and MRI image segmentation [15][16][17][18][19][20][21]. Particularly in the medical field, these techniques have been proved invaluable in predicting…”
Section: Introductionmentioning
confidence: 99%